Non-isothermal decomposition kinetics of theobromine in nitrogen atmosphere - Kamel, Laila Tosson (European Journal of Chemistry, 2015)
The non-isothermal decomposition process of theobromine under nitrogen atmosphere was studied using the differential thermal analysis (DTA), from room temperature up to 500 °C, at heating rates, 5, 15 and 20 °C/min. The results showed that theobromine decomposes in two steps. The kinetic analysis of the first decomposition step was performed using Kissinger, Friedman, Flynn-Wall-Ozawa, and Kissinger-Akahira-Sunose isoconventional methods. The kinetic model was determined using Šatava-Šesták method. Results showed that the non-isothermal decomposition mechanism of theobromine corresponds to nucleation and growth, following the Avrami-Erofeev equation. The forms of the integral and differential equations for the mechanism function are g(α)=(-ln(1-α))2/3 and f(α)=(3/2)(1-α)(-ln(1-α))1/3, respectively. Thermodynamic parameters of the non-isothermal decomposition process, change of enthalpy (ΔH), change of entropy (ΔS), and change of Gibbs free energy (ΔG) values were calculated.